Zatočenici mita / Prisoners of Myth: Osvrt na knjigu Latinke Perović "Dominantna i neželjena elita: Beleške o intelektualnoj i političkoj eliti u Srbiji (XX-XXI vek) / Book Review 'Dominant and Unwelcome Elite': Notes on Intellectual and Political Elite in serbia (20th and 21st Centuries) by Latinka Perović - Busuladžić, Adisa (Pregled: časopis za društvena pitanja / Periodical for social issues, 2016)
This text is review of a book Dominant and unwelcome elite: Notes on intellectual and political elite in Serbia (20th and 21st centuries) by Latinka Perović, Dan Graf, Beograd, 2015.